Proportions of prognostic scoring models among ICU patients receiving enteral nutrition - Mousavi Jazayeri, Seyed Mohammad Hosein; Ostadrahimi, Alireza; Hashemzadeh, Shahryar; Safaiyan, Abdolrasoul; Salehpour, Firouz; Barati, Meisam; Azizi-Soleima, Fatemeh (Progress in Nutrition, 2018)
Background: The present study was designed to define the proportions of effective factors associated with feeding among intensive care unit (ICU) patients in predicting the Simplified Acute Physiology Score II (SAPS II) and Sequential Organ Failure Assessment (SOFA). Material and Methods: In a double blinded, randomized clinical trial, 32 critically ill patients were randomly assigned to one of four groups: early-opened, delayed-open, early-closed, and delayed-closed enteral nutrition (EN). SAPS II and SOFA were calculated on day 1, 3, 5 and 7 and the contribution rates of different variables were determined. Results: The proportion of time of the provision of EN (Early vs. Delayed) and system for the delivery (Open vs. Closed) in determining SAPS II was 48% and 3% respectively. The proportion of time of the provision of enteral feeding in defining SOFA was 14%. Age and gender had no impact on determining SOFA. Proportion of system for the delivery of EN and time in defining SOFA was 47% and 24%, respectively. Conclusion: Time of the provision of EN is the most effective factor in determining SAPS II and SOFA in critically ill patients admitted in ICU, rather than the system of delivery. Clinical Relevancy Statement: Intensive care units (ICU) scales play important roles in decision making and are consisted of well-known factors. We found that other factors like early administration of enteral nutrition (EN) and type of formula are also crucial in predicting the score of these scales. This finding is clinically relevant for guiding health care staff to make the best decision for choosing an efficient time and system for delivery of EN.